Simultaneous catalyzing and reinforcing effects of imidazole-functionalized graphene in anhydride-cured epoxies - Liu, Wanshuang (2013)
In this study, an imidazole-functionalized graphene (G-IMD) was prepared from graphene oxide by a facile one-pot method. The functionalized graphene not only showed improved organic compatibility but also could simultaneously play the roles of a cure accelerator and reinforcement for anhydride-cured epoxies. Our results showed that G-IMD could successfully catalyze the curing reaction without the addition of any routine accelerator. Thermal and mechanical properties of the epoxy–G-IMD nanocomposites were systematically studied at different filler loadings. Compared with neat epoxy resin, tensile strength and Young's modulus of the nanocomposites were enhanced by 97% and 12%, respectively, at only 0.4 wt% G-IMD loading. Dynamic mechanical analysis and electron microscopic results revealed that the drastic improvements in mechanical properties could be attributed to the homogeneous dispersion of G-IMD and covalent bonding at the interface, which effectively improved the efficiency of load transfer between the matrix and graphene.